Pengembangan Program Internet Of Things pada Coffee Vending Machine - Kiki Krisdayanti; M. Soekarno Putra (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Internet of things isdevelopments that are able to optimize human life through the help of sensors and artificial intelligence using the internet as a means and connecting devices to devices as well as devices to humans. The problem encountered is how to create a business without any physical contact between the seller and the buyer and be able to control sales remotely. Therefore, an IoT-based vending machine is needed with the aim of making it easier for vending machine owners to see transactions in the form of how many products have been sold or are still available on the vending machine and the volume in the tank. Utilization of the internet combined with a coin acceptor and Arduino Uno microcontroller can make buying and selling transactions without physical contact, the buyer only interacts with the vending machine.